2022
DOI: 10.3390/ani12050588
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Protein Restriction in Primiparous Beef Heifers during Mid- and/or Late-Gestation on Progeny Feedlot Performance and Carcass Characteristics

Abstract: This study investigated the impacts of metabolizable protein (MP) restriction in primiparous heifers during mid- and/or late-gestation on progeny performance and carcass characteristics. Heifers were allocated to 12 pens in a randomized complete block design. The factorial treatment structure included two stages of gestation (mid- and late-) and two levels of dietary protein (control (CON); ~101% of MP requirements and restricted (RES); ~80% of MP requirements). Half of the pens on each treatment were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…There are studies that reported an increase in thickness in the groups that underwent restriction, such as the two presented above, which probably happen due to a compensatory growth in adipose tissue [8]. However, other studies did not observe differences in fat thickness but observed differences in REA [12,37,43]. At the same time, other works, such as this one, did not find differences in any of the two characteristics, as in Wilson et al [44] and Mulliniks et al [45].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There are studies that reported an increase in thickness in the groups that underwent restriction, such as the two presented above, which probably happen due to a compensatory growth in adipose tissue [8]. However, other studies did not observe differences in fat thickness but observed differences in REA [12,37,43]. At the same time, other works, such as this one, did not find differences in any of the two characteristics, as in Wilson et al [44] and Mulliniks et al [45].…”
Section: Discussionmentioning
confidence: 89%
“…When searching for studies in the literature, once again, scattered results were found. Some studies suggest there is no difference between treatments for ADG in the feedlot [ 43 , 44 ], while in Mulliniks et al [ 45 ], animals whose mothers were able to maintain or gain weight during late pregnancy had higher ADG in the feedlot.…”
Section: Discussionmentioning
confidence: 99%
“…This is also repeated for the other characteristics, such as weight and performance. Some studies have already reported similarities between treatments for these traits in steer calves whose mothers were given prepartum supplementation [51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…In beef cattle production, fetal programming may affect several phenotypes [ 13 , 14 , 15 , 16 ]. Nevertheless, the mechanisms that involve the responses to each prenatal environment, breed, and other variables have not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%